2014
DOI: 10.1177/1352458514557304
|View full text |Cite
|
Sign up to set email alerts
|

Human interferon regulatory factor 5 homologous epitopes ofEpstein-Barrvirus andMycobacterium aviumsubsp.paratuberculosisinduce a specific humoral and cellular immune response in multiple sclerosis patients

Abstract: Our data demonstrated that both EBV and MAP epitopes elicit a consistent humoral response in MS patients compared to HCs, and that the aforementioned peptides are able to induce a T-cell-mediated response that is MS correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 38 publications
0
58
1
3
Order By: Relevance
“…Molecular mimicry and SLC11A1 associations are central to this association as well (40, 41). MAP has been associated with Epstein–Barr virus (EBV – thought to be one of the triggers of MS) (44): peptides of each microorganism (MAP and EBV) cross react with anti-myelin basic protein (MBP) (43) and interferon regulatory factor 5 (IRF5) in MS patients (48). Interferon-beta therapy influence antibody response against MAP (49).…”
Section: Map and Multiple Sclerosismentioning
confidence: 99%
“…Molecular mimicry and SLC11A1 associations are central to this association as well (40, 41). MAP has been associated with Epstein–Barr virus (EBV – thought to be one of the triggers of MS) (44): peptides of each microorganism (MAP and EBV) cross react with anti-myelin basic protein (MBP) (43) and interferon regulatory factor 5 (IRF5) in MS patients (48). Interferon-beta therapy influence antibody response against MAP (49).…”
Section: Map and Multiple Sclerosismentioning
confidence: 99%
“…These MAP antigens are considered to be a weapon to impair the most powerful host cellular immunological defenses and to achieve chronic infection in cattle [35]. The phenomenon that stimulates host Th1 and Th2 in different stages of infection [18] is very similar to that in human leprosy [38, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…Experimental CD-type colitis induced with the MAP antigen also suggests the potency of MAP to induce CD [4]. MAP was also linked with others autoimmune diseases such as type 1 diabetes, multiple sclerosis, and Hashimoto's thyroiditis [1518]. …”
Section: Introductionmentioning
confidence: 99%
“…BAFF plays an essential role in B cell homeostasis and has been associated with different types of autoimmune diseases. In recent years, Mycobacterium avium subspecies paratuberculosis (MAP) has been associated to MS in Sardinia-an island with particularly high prevalence of the disease (Frau et al 2013;Mameli et al 2014;Cossu et al 2015). We previously reported that IFN-β enhances the immunological response against MAP .…”
Section: Main Textmentioning
confidence: 98%